SERANGGA PENGUNJUNG BUNGA PADA TANAMAN KELAPA SAWIT DI PERKEBUNAN PTPN VI KECAMATAN PANGKALAN KOTO BARU - Elijonnahdi, Elijonnahdi; Sitepu, Nurlela; Zeswita, Armein Lusi; Rahmi, Silatur (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2021)
Oil palm flowers release volatile compounds that can attract insects. The types of insects that visit oil palm flowers are diverse, not all who visit the flowers are able to act as pollinators. This study aims to determine the types of insects (Insects) flower visitors to oil palm (Elaeis guineensis Jacq.) In the PTP Nusantara VI Kecamatan Pangkalan Koto Baru. This research is a descriptive study. The research method is survey research. This research was conducted at 4 points of the research plot. The research sample was obtained by installing a Batterfly bait trap in the research area, then the identification was carried out in the laboratory using the book Kanisius (1991) and Entomologyi Pertanian (Jumar, 2000). From the results of the research using the Batterfly bait trap, it was found that the insects consisted of 3 orders, namely the Lepidoptera Order, the Hemiptera Order, and the Ortopthera Order where each order consisted of 1 type of family. The family found from the Lepidoptera Order is the Nymphalidae Family which consists of 6 species, namely Junonia hedonia 1 Individual, Ypthima pondacus 1 individual, Ypthima baldus 5 individual, Mycalesis janardana 3 individual, Elymnias hypermnestra 2 individuals, and types of Elymnias nesaea 1 individuals. From the Hemiptera Order, 1 family was obtained, namely, Pentatomidae which consisted of 1 type, namely the Picromerus bidens 1 individual type and the Orthopthera Order consisting of 1 family, namely Blattidae of the Periplaneta australasiae type as many 4 individuals, a total of 18 individuals were obtained.